What macroeconomic variables drive the stock returns of Austrian financial institutions? - Ligocká, Marie; Stavárek, Daniel (Univerzita Pardubice, 2018)
The stock prices of companies are influenced by many variables; the predominant ones are macroeconomic factors. The objective of this paper is to analyze the existence of a relationship between select macroeconomic variables and the stock returns of financial sector companies listed on the Vienna Stock Exchange. The institutions that were chosen are CA Immobilien Anlagen, Erste Group Bank AG, Immofinanz AG, Raiffeisen Bank International AG, Uniqa Insurance Group AG and Vienna Insurance Group AG. The focus is on Austria due to the lack of empirical literature on stock prices, stock returns and the indicators that influence them. A time series with a quarterly frequency is used to examine the occurrence of long term and short-term relationship links using the Johansen cointegration test and the Vector Error Correction Model (VECM). The empirical estimates are calculated for the 2005 – 2015 period, which includes the global financial crisis. Our main finding is that the macroeconomic factors used have a primarily negative impact on the stock returns of the select institutions.
Keywords: financial sector; macroeconomic variables; Austria; cointegration; global financial crisis.; G01; O52; F41; E000; C58